Three new species of Gnaptorina Reitter (Coleoptera, Tenebrionidae: Blaptini) from Tibet, China - Shi, Ai-Min (Zootaxa, 2013)
Three new species of Gnaptorina Reitter, 1887, G. (Hesperoptorina) medvedevi, sp. nov., G. (H.) dongdashanensis, sp. nov. and G. (H.) cuonaensis, sp. nov. are described from Tibet, China. A key to the known species of the subgenus Hes-peroptorina is given.